Historical and Ethnographic Approaches in Qualitative Research - Muhammad Adriansyah Siregar; Muhammad Amin; Niswatul Azizah Nasution; Rahma Winanda; Syfa Nailul Husnah; Nur Hasanah; Andriyadi Marta; Putri Syahri (International Journal of Educational Research Excellence (IJERE), 2023)
As an effort to carry out research, research methods have a very important role in getting answers to the problems being researched. In addition, research also occupies the most important position with regard to science, which means that this step is aimed at developing and continuing research in the future so that it does not become extinct. In qualitative research, there are many methods used to collect data as research sources, both from text and non-text. The results of qualitative research are generally in the form of a research design based on the findings of previous researchers and are not in the form of statistical figures. Qualitative research is explanatory in nature and leads to an analytical approach that emphasizes facts on the problems studied and is also known as a method that proceeds from a specific discussion to a general focus. This process is then highlighted in qualitative research to thoroughly explain the series and results of the research so that it is easy for researchers and academics to understand.